2004
DOI: 10.1152/jn.00597.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weakness on Symmetrical Bilateral Grip Force Exertion in Subjects With Hemiparesis

Abstract: It has been shown that, in a bilateral force-matching task, subjects presenting weakness in one limb produce a lower force in the weakened limb even though they subjectively perceive that they are exerting the same force. The aim of this study was to verify whether subjects with hemiparesis produced asymmetrical forces during a bilateral submaximal grip task and whether this asymmetry is related to weakness of the paretic limb. Fifteen subjects with hemiparesis and 15 healthy subjects were recruited. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
3
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
(32 reference statements)
7
38
3
6
Order By: Relevance
“…According to previous studies, the asymmetries observed in hemiparetic subjects seem to be related to the desire to produce symmetrical levels of effort. 21,22 Bertrand et al 22 proposed the principle of bilateral matching effort to explain the strategy chosen by hemiparetic individuals when performing bilateral matching tasks at the upper limbs. Also, Simon and Ferris 21 demonstrated in hemiparetic subjects that, during an isometric force-matching task on a leg press machine, there was no significant difference between limbs when normalizing the forces produced by those obtained in bilateral maximum voluntary contractions.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the asymmetries observed in hemiparetic subjects seem to be related to the desire to produce symmetrical levels of effort. 21,22 Bertrand et al 22 proposed the principle of bilateral matching effort to explain the strategy chosen by hemiparetic individuals when performing bilateral matching tasks at the upper limbs. Also, Simon and Ferris 21 demonstrated in hemiparetic subjects that, during an isometric force-matching task on a leg press machine, there was no significant difference between limbs when normalizing the forces produced by those obtained in bilateral maximum voluntary contractions.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this observation is that the hemiparetic participants scaled their effort to their maximal strength, as shown in single or multiarticulated efforts. 21,22 The idea of using the sense of effort in hemiparetic gait was first presented in a previous work by the authors. 9 The presence of similar levels of effort between affected and unaffected sides can also provide a new explanation for the asymmetrical gait pattern observed in stroke individuals.…”
Section: Discussion Clinical Evaluationmentioning
confidence: 99%
“…On the contrary, reduced motility and proprioceptive impairments are themes of discussion which involve both groups of patients. Motor impairment of the ''other side leg'' may be a consequence of abnormal postural stabilization [3,16]. In HS patients, the force produced by the ''ipsilateral limb'' is reduced because of the difficulty in supplying contralateral stabilization using the paretic side owing to weakness, spasticity and abnormal postures [19].…”
Section: Discussionmentioning
confidence: 99%
“…About this topic, there is a reduced number of studies underlining the role of peripheral mechanisms [2]. For instance, an abnormal postural stabilization too may play a role in ipsilateral motor impairment [3,16].…”
Section: Introductionmentioning
confidence: 99%